X‐Light: an open‐source software written in Python to determine the residual stress by X‐ray diffraction. Issue 4 (16th July 2021) - Pham, Tu-Quoc-Sang; Geandier, Guillaume; Ratel-Ramond, Nicolas; Mareau, Charles; Malard, Benoit
Abstract : Software for residual stress determination by X‐ray diffraction is introduced. Abstract : X‐Light is an open‐source software that is written in Python with a graphical user interface. X‐Light was developed to determine residual stress by X‐ray diffraction. This software can process the 0D, 1D and 2D diffraction data obtained with laboratory diffractometers or synchrotron radiation. X‐Light provides several options for stress analysis and five functions to fit a peak: Gauss, Lorentz, Pearson VII, pseudo‐Voigt and Voigt. The residual stress is determined by the conventional sin 2 ψ method and the fundamental method.